Mesenchymal stem cells for the cell-based therapy of type 1 diabetes : an experimental approach - Limbert, Catarina de Castro Sobral Blanco, 1964- (2010)
Tese de doutoramento, Medicina (Fisiopatologia), Universidade de Lisboa, Faculdade de Medicina, 2011